1977
DOI: 10.1136/jnnp.40.7.666
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid enzymes in acute brain injury. 2. Relation of CSF enzyme activity to extent of brain injury.

Abstract: SUMMARY The value of CSF enzyme estimations as indices of the extent of brain damage was studied in the experimental situation. Standard cold lesions of different severity were induced in cats. The activities of the enzymes CPK, HBDH, LDH, GOT, and ChE were studied at half hour intervals in the cerebrospinal fluid (CSF). The ventricular and cisternal fluid pressure, and the arterial blood pressure were monitored continuously. Significantly higher enzyme levels were found in the animals with more severe injurie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Hypoxia causes release of CPK from damaged cells and increased CPK has been found in the cerebrospinal fluid in acute cerebral vascular accidents, encephalitis and head trauma, z2-z4 Cerebrospinal fluid CPK has several advantages as an index of brain damage, since it is principally derived from the central nervous system, does not normally cross the blood-brain barrier, 23 is not found in red blood cells which may contaminate cerebrospinal fluid samples, 24 and appears to be correlated with the severity of central nervous system damage. 22 Cerebrospinal fluid CPK increased to over three times the control during combined hyperventilation and hypotension, providing further evidence of cerebral hypoxia. The failure of cerebrospinal fluid lactate, lactate/pyruvate ratio, and CPK to fall until after hyperventilation was discontinued in group Ill animals suggests that the decreased cerebral oxygen supply resulting from combined hyperventilation and hypotension continues even after blood pressure returns to normal, as long as Paco2 remains near 3.33 kPa (25 mm Hg).…”
Section: Cerebrospinal Fluid Creatine Phosphokinasementioning
confidence: 79%
“…Hypoxia causes release of CPK from damaged cells and increased CPK has been found in the cerebrospinal fluid in acute cerebral vascular accidents, encephalitis and head trauma, z2-z4 Cerebrospinal fluid CPK has several advantages as an index of brain damage, since it is principally derived from the central nervous system, does not normally cross the blood-brain barrier, 23 is not found in red blood cells which may contaminate cerebrospinal fluid samples, 24 and appears to be correlated with the severity of central nervous system damage. 22 Cerebrospinal fluid CPK increased to over three times the control during combined hyperventilation and hypotension, providing further evidence of cerebral hypoxia. The failure of cerebrospinal fluid lactate, lactate/pyruvate ratio, and CPK to fall until after hyperventilation was discontinued in group Ill animals suggests that the decreased cerebral oxygen supply resulting from combined hyperventilation and hypotension continues even after blood pressure returns to normal, as long as Paco2 remains near 3.33 kPa (25 mm Hg).…”
Section: Cerebrospinal Fluid Creatine Phosphokinasementioning
confidence: 79%
“…The highest tissue CK-BB content was found in the brain cortex and capsula interna, whde only small amounts were measured in the pons, cerebellum and medulla oblongata (32). Therefore, a small focal lesion in a functionally important region of the brain may cause severe impairment with minimal enzyme release (15,33). On the other hand, the concentration of CK-BB in the CSF changes rapidly during the first hours of brain injury (19,29), thus the results depend on the time of collection of CSF.…”
Section: Discussionmentioning
confidence: 99%
“…Along that line, it has previously been reported that cerebrospinal fluid (CSF) transaminases (SGOT, ALAT) were elevated in hypotensive anaesthesia (≤50 mmHg) 23,24 . In non‐human studies, Maas 25 reported that CSF enzymes were elevated in acute brain injury in rats. Also, the relationship between low blood pressure and tau protein is recognized in Alzheimer's Disease 26 …”
Section: Discussionmentioning
confidence: 87%